Pengaruh Celebrity Endorser dan Kualitas Produk terhadap Keputusan Pembelian melalui Citra Merek pada Kosmetik Wardah di Kota Semarang (Universitas Negeri Semarang, 2015)
The purpose of this study was to determine the effect of direct and indirect celebrity endorser, product quality and brand image as an intervening variable on purchase decisions. The population of research are users Wardah cosmetics in the city of Semarang. Total sample of 116 respondents with asidental sampling. Data obtained by questionnaire. Celebrity endorser study variables (X1), product quality (X2), brand image (Z), and purchasing decisions. Data were analyzed by descriptive persentif percentage and path analysis. The results showed that the variables celebrity endorser (X1) and product quality (X2) directly influence the purchase decision. Variable celebrity endorser (X1) and product quality (X2) indirect effect on purchasing decisions. Test results from path analysis showed that the celebrity endorser (X1) influence on purchase decisions through brand image and product quality (X2) effect on purchase decisions through brand image, so that it can be said that the brand image mediates the influence of celebrity endorser and product quality on purchasing decisions.